29th International Conference on Ocean, Offshore and Arctic Engineering: Volume 1 2010
DOI: 10.1115/omae2010-20386
|View full text |Cite
|
Sign up to set email alerts
|

Hull Optimization of the Unmanned AGaPaS Rescue Vessel

Abstract: Crew safety is a key parameter for any seagoing mission. Although today’s standards are high, occasionally people go overboard while working on deck. In this case the probability of survival remains low. The joint research project “AGaPaS” [1] aims to significantly increase the chances of survival for a drifting person. Its main objective is to develop a self activating, partially autonomously operating rescue system, able to search, find and rescue people gone overboard. A crucial part of the system is a remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The front arch is connected to the rescue platform and the suspension system by spherical joints, and the rear arch is connected to the left and right pontoons by articulation joints with rotational degrees of freedom in the horizontal and vertical planes, which constitute the articulated system of the vessel. According to the application and rescue environment of the rescue vessel [24], the specific dimensions of the rescue vessel designed in this research are shown in Table 1. According to the application and rescue environment of the rescue vessel [24], the specific dimensions of the rescue vessel designed in this research are shown in Table 1.…”
Section: Overall Structure Of Rescue Vesselmentioning
confidence: 99%
See 1 more Smart Citation
“…The front arch is connected to the rescue platform and the suspension system by spherical joints, and the rear arch is connected to the left and right pontoons by articulation joints with rotational degrees of freedom in the horizontal and vertical planes, which constitute the articulated system of the vessel. According to the application and rescue environment of the rescue vessel [24], the specific dimensions of the rescue vessel designed in this research are shown in Table 1. According to the application and rescue environment of the rescue vessel [24], the specific dimensions of the rescue vessel designed in this research are shown in Table 1.…”
Section: Overall Structure Of Rescue Vesselmentioning
confidence: 99%
“…According to the application and rescue environment of the rescue vessel [24], the specific dimensions of the rescue vessel designed in this research are shown in Table 1. According to the application and rescue environment of the rescue vessel [24], the specific dimensions of the rescue vessel designed in this research are shown in Table 1. The novel idea of the suspension system mainly comes from the automobile industry.…”
Section: Overall Structure Of Rescue Vesselmentioning
confidence: 99%
“…Kurowski et al [194] developed a satellite-guided SAR system, to be used in special ships and offshore platforms in case a person falls overboard. It consists of three main components: (1) A vest with an Automatic Identification System (AIS), worn by every crew member of a ship or offshore platform; (2) An autonomous twin-hull catamaran USV, referred to as the “rescue vessel” (described in detail in [195,196]); A satellite-aided control station. When a person falls overboard, the AIS vest activates upon contact with the water, and the SAR process starts.…”
Section: Usv Applications For Preventive Maintenance and Disaster mentioning
confidence: 99%
“…Thus, the ship does not need to stop to lower the rescue boat. 2 After the release, the rescue vessel moves autonomously as fast as possible to the POB and maintains a minimum safety distance to the POB. At this point, an operator on board the parent ship or offshore platform takes over the control of the rescue vessel.…”
Section: Search-and-rescue-scenariomentioning
confidence: 99%
“…The retrieval of the POB takes place via a hydraulically operated net basket, which is fixed at its rear edge. The hull speed is about 5.5 knot, and the free fall accelerations from 7.5 m height can be reduced to approximately 6.5 g. 2 The full-scale vehicle is about 4.5 m long and almost 2.3 m wide. Two electrical podded drives move the vehicle, getting its power from 48 V lithium batteries.…”
Section: Design and Automation Of The Rescue Vesselmentioning
confidence: 99%